2003
DOI: 10.1194/jlr.m200477-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fluid mechanical stresses and plasma constituents on aggregation of LDL

Abstract: LDL aggregates when exposed to even moderate fluid mechanical stresses in the laboratory, yet its half-life in the circulation is 2-3 days, implying that little aggregation occurs. LDL may be protected from aggregation in vivo by components of plasma, or by a qualitative difference in flows. Previous studies have shown that HDL and albumin inhibit the aggregation induced by vortexing. Using a more reproducible method of inducing aggregation and assessing aggregation both spectrophotometrically and by sedimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
(25 reference statements)
0
9
0
Order By: Relevance
“…These aggregated LDLs were avidly ingested and degraded by macrophages, converting them into cholesterol ester-rich foam cells. Later studies using fluid stress model confirmed time-dependent LDL aggregation, which was monitored by light attenuation and sedimentation (96, 97). Notably, LDL aggregation was partially inhibited in total plasma, apparently due to the protective effects of other apolipoproteins that are also expected to inhibit LDL aggregation in circulation (described above).…”
Section: Physical Perturbationsmentioning
confidence: 93%
See 1 more Smart Citation
“…These aggregated LDLs were avidly ingested and degraded by macrophages, converting them into cholesterol ester-rich foam cells. Later studies using fluid stress model confirmed time-dependent LDL aggregation, which was monitored by light attenuation and sedimentation (96, 97). Notably, LDL aggregation was partially inhibited in total plasma, apparently due to the protective effects of other apolipoproteins that are also expected to inhibit LDL aggregation in circulation (described above).…”
Section: Physical Perturbationsmentioning
confidence: 93%
“…Khoo et al (41) showed that albumin reduced LDL aggregation upon vortexing. Talbot et al (96) showed that at physiological concentrations, albumin reduced flow-induced LDL aggregation. Notably, heat-denatured and fatty acid-stripped albumin was particularly effective in protecting LDLs from aggregation.…”
Section: Proteins Lipids Small Molecules and Polymers That Promotementioning
confidence: 99%
“…Larger lipid aggregates are then formed that flocculate and generate turbidity [8][9][10]. On one hand, LDL-aggregation is described to be prevented by both HDL [10] and albumin [8]. On the other hand, aggregated LDL is thought to be taken up by macrophages more easily [9].…”
Section: Discussionmentioning
confidence: 99%
“…Here, the vesicular structure of LDL-cholesterol particles is degraded by mechanical stress. Larger lipid aggregates are then formed that flocculate and generate turbidity [8][9][10]. On one hand, LDL-aggregation is described to be prevented by both HDL [10] and albumin [8].…”
Section: Discussionmentioning
confidence: 99%
“…It was reported by some workers that LDL subjected to vortexing forms self-aggregates (Khoo et al, 1988(Khoo et al, , 1990Guyton et al, 1991;Pentikainen et al, 1996;Xu and Lin, 2001). LDL aggregation involves hydrophobic interactions (Talbot et al, 2003). LDL structure is profoundly disrupted by vortexing (Guyton et al, 1991).…”
Section: Discussionmentioning
confidence: 99%